PERAN KOMISARIS DALAM RANGKA MEMBANGUN GOOD CORPORATE GOVERNANCE DI BANK PEMBIAYAAN RAKYAT SYARIAH - Sugeng Riyadi; Fetri Fatorina; Endang Eko Wati (Economics, Social, and Humanities Journal (Esochum), 2023)
BPRS has a clear organizational structure in accordance with its competence. One of the management in a BPRS is the existence of commissioners who contribute a lot in the development of a BPRS. BPRS will develop when the commissioners are able to carry out their roles properly. Vice versa, BPRS development will be hampered when the commissioners do not understand their role. The Board of Commissioners must be able to carry out good corporate governance to realize company performance, maintain good relations with stakeholders, and in the long term maintain the trust of shareholders and stakeholders so that the company's competitiveness in the business world can be maintained. This type of research uses normative juridical, namely research conducted by examining library materials which are secondary legal materials. The data analysis method applied in this research is qualitative analysis. The results of the study, in order to realize good GCG in the BPRS, it can be said that the board of commissioners is the core or heart of the BPRS governance system. The role of the board of commissioners is very important for the running of a BPRS. The board of commissioners is required to know and understand the regulations of the PT Law, the Sharia Bank Law, BI Regulations and Circulars, OJK Regulations and Circulars and DSN Fatwas. The commissioner in Law Number 21 of 2008 has a role as a supervisor of BPRS governance starting from supervising compliance with applicable laws to the process of evaluating BPRS governance. The explanation of the role of the BPRS is explained in article 29 of Law Number 21 of 2008 concerning Islamic Banking.